Des bois dans les Maisons. Rôles du système social dans la forêt rurale des paysages des Coteaux de Gascogne (Sud-ouest de la France) - Marc Deconchat; Julien Blanco; Émilie Andrieu; Anne Sourdril (Projets de Paysage)
The landscapes of South-Western France are dotted with many small woodlots that have important ecological, socioeconomic, and cultural functions for local communities. This article presents an interdisciplinary synthesis of work conducted over the last thirty years on these woodlots in the Atelier Pygar Zone (Pyrenees-Garonne). It focuses on the benefits of closely associating approaches of landscape ecology and human and social sciences to understand the current state and recent history of these woodlots and to help in designing landscape projects adapted to local contexts. First, we present the specific ecological characteristics of the woodlots, which are distinguished by the rich diversity of ligneous species and their contribution to numerous ecosystem services. However, these characteristics do not fully explain why these woodlots have been maintained in the landscapes studied whereas they tend to disappear from agricultural landscapes in favour of larger forested areas. Ethnographic research provides a key to understanding this paradox by showing that the presence of woodlots in the Coteaux de Gascogne was the result of strong social rules relating to the House Society system which favours the maintenance of woodland diversity close to farms while producing useful goods and services. The future of these woodlots is nevertheless uncertain given the changes in the current agricultural and forestry context. A better understanding of the links between agriculture and woodlands, notably by introducing the concept of the "rural forest" could be an asset for the development of territories such as the Coteaux de Gascogne.